PENGARUH INJECTION SEMEN PADA DAYA DUKUNG TANAH LEMPUNG LUNAK - Zaki, M (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2022)
In countries that are dominated by islands, there tends to be a lot of soft soil (fat clay) and alluvial, this is one of the problems that often occurs and is not profitable for the small bearing capacity and settlement that occurs. The grouting method or Soil Injection Cement is a method of soil improvement by injecting the cement base material into the soil with the aim of increasing the stability of the existing soil and rock. Cement is widely used in geotechnical engineering and geo-environment applications, namely in the stabilization of soft soils or soft clays where their performance is affected by exposure to chemicals that exist as mixtures such as zeolites. Zeolite is hydrated aluminum silicate with sodium cation as a means to increase the durability of cement-based materials, especially for sulfate applications. Research carried out in verifying the potential for improvement or stabilization of soft soils, soft clays and expansive soils can make a good contribution to technological development. This research was only conducted on the analysis of the bearing capacity of clay and its behavior towards the use of cement mixed with bentonite and cement grouting with zeolite. The effect of this use is very clear on the characteristics of the soil and the material using the unconfined test (UCT). The results of this study indicate a fairly good difference in observing the behavior between cement-zeolite and cement-bentonite, which is a significant addition to the compressive strength value by using cement mixed with zeolite.